Comparative ontogeny, processing, and segmental distribution of the renal chloride channel, ClC-5. - Jouret, F; Igarashi, T; Gofflot, F; Wilson, P; Karet, F; Thakker, R; Devuyst, O (2004)
BACKGROUND: The renal chloride channel ClC-5, which is responsible for Dent's disease, is coexpressed with the vacuolar H+-ATPase in proximal tubules (PT) and alpha-type intercalated cells (IC) of the mature kidney. Neonatal cases of Dent's disease suggest that ClC-5 distribution must be acquired before birth. However, the ontogeny of ClC-5, and its processing and segmental distribution with respect to related proteins during nephrogenesis remain unknown. METHODS: Immunoblotting, real-time polymerase chain reaction (RT-PCR), immunostaining, and deglycosylation studies were used to investigate the expression, distribution, and maturation of ClC-5 during mouse and human nephrogenesis, in comparison with H+-ATPase, type II carbonic anhydrase (CAII), and aquaporin-1 (AQP1). RESULTS: An early induction (E13.5-E14.5) of ClC-5 was observed in mouse kidney, with persistence at high levels through late nephrogenesis. This pattern contrasted with the progressive expression of H+-ATPase and AQP1, and the postnatal upregulation of CAII. Immunostaining showed expression of ClC-5 in ureteric buds and, from E14.5, its location in developing PT. From E15.5, ClC-5 codistributed with H+-ATPase in PT cells and alpha-type IC. In the human kidney, ClC-5 was detected from 12 gestation weeks; its distribution was similar to that observed in mouse, except for a later detection in IC. Although mouse and human ClC-5 proteins are glycosylated, biochemical differences between fetal and adult proteins were observed in both species. CONCLUSION: The segmental expression of ClC-5 and H+-ATPase is essentially achieved during early nephrogenesis, in parallel with the onset of glomerular filtration. These data give insight into PT and IC maturation, and explain early phenotypic variants of Dent's disease.